Diversidad de crustáceos de la Cuenca hidrográfica Baja del Río Moche – La Libertad 2015. - Ruiz Herrera, Irene del Rosario (2016)
The objective was to determine the diversity of crustaceans of the lower watershed of Rio Moche, between May and October 2015 several samples in 4 specific points were made, collecting 50 samples for examination. It was determined a total of 3 crustacean species, one of them belong to decapod order, order sub Reptantia, family Pseudothelphusidae, Hypolobocera gender and species H. chiliensis and two belonging to the decapod order, order sub natantia, family Palaemonidae, gender Cryphiops and species C. caementarius (Molina, 1872), as well as the gender Macrobrachium, species M. inca (Holthuis, 1952); it was determined a low richness and low numerical abundance._x000D_ Keywords: diversity, crustaceans, Lower river Moche.